Language difficulties vis-à-vis the communicative abilities among college freshmen students of Jose Rizal Memorial State College, Main Campus, Dapitan City - Telen, Jay D. (The Threshold: the Official Research Journal of Jose Rizal Memorial State University, Zamboanga del Norte, 2007)
The study aimed to find out the difference on the level of language difficulties on terms of grammar, vocabulary, pronunciation and planning among College freshmen students of Jose Rizal Memorial State College (JRMSC) and the difference on the level of communicative abilities to develop a functional learning kit. A customized questionnaire was administered to 265 JRMSC freshmen students during the second semester of school year 2004-2005. The analysis of variance was the main statistical test. The study revealed that freshmen students, when grouped according to Colleges, differed significantly in terms of language difficulties since the highest discrepancy was noted and appeared to be in terms of vocabulary followed by pronunciation (oral) and least in pronunciation (written). However, there was no significant difference in terms of communicative abilities.